PERKEMBANGAN ILMU PENGETAHUAN PADA MASA BANI ABBASIYAH DENGAN MEDIA AKUN VIDEO SCRIBE YOUTUBE - Rofi’ah Rofi’ah (Asaatidzah, 2022)
Based on initial observations of the teaching and learning process and learning outcomes, class VIII E students tend to be passive and lazy to read history and have not yet reached KKM, and the use of media in teaching and learning activities in class is still lacking. Therefore, the researcher applied Audio Visual media (Video Scribe you tobe) as a tool in teaching and learning activities to find out whether the use of the YouTube video scribe account media was able to improve Islamic education learning outcomes on Islamic history material in class VIII E SMPN 14, Cirebon. The methodology used is CAR, taking the form of collaborative research between researchers and teachers. This research was carried out in two cycles where each cycle consisted of four main stages, namely: planning, implementing activities, observing (observation) and reflecting. Based on the results of the research that has been done, it can be concluded that the application of YouTube video scribe media to PAI subjects on the history of the development of science during the Abasiyyah period can improve student learning outcomes. The increase in student learning outcomes can be proven from the value of student learning outcomes each cycle has increased.